Violent women in Spanish TV ads: Stereotype reversal or the same old same old? - Pennock-Speck, Barry (Discourse & Communication, 2016)
Why did different agencies, promoting diverse products, create three ads featuring violence perpetrated by women on their rather immature and submissive male partners in order to sell their products? I posit that the female viewers connect subconsciously with the image of the proactive female protagonists through the psychological mechanism in which we identify with ‘our like’ on the screen. This, in turn, allows for the projection of ‘common ground’, a positive politeness strategy, to favourably dispose the female audience towards the protagonists and, by extension, the products advertised. The success of these ads depends on women viewers identifying with the apparently dominant female protagonists – a case of ‘gender stereotype reversal’. However, I put forward that through the violent modification of their partners’ behaviour, the women become responsible for them, and so the ads convey the common gender stereotype of women as carers.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNzUwNDgxMzE2NjM4MTUx